Tethered to the cross: the life and preaching of Charles H. Spurgeon - Breimaier, Thomas (IVP Academic, an imprint of InterVarsity Press, 2020)
"What guided English Baptist minister Charles H. Spurgeon's reading of Scripture? Tracing the development of Spurgeon's thought and his approach to biblical hermeneutics throughout his ministry, theologian and historian Thomas Breimaier argues that Spurgeon viewed the entire Bible through the lens of the cross of Christ"--